THE EFFECT OF TOUCH THERAPY ON NUTRITION STATUS AND THE DEVELOPMENT OF INFANTS - siti indatul laili; Tri Ratnaningsih; Tri Peni (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
Infancy started from 0-12 months which was characterized by rapid growth and physical changes accompanied by changes in nutritional needs to optimize the growth and development of the baby by providing touch, motion and other stimulation combinations. The research was purposed to know the effect of Touch Therapy on nutritional status and development on infants in Gayaman Village, Mojokerto Regency. The research design used one group pre-post test design. The population were infants in Gayaman Village, Mojokerto Regency, 70 respondents. The sample was 69 infants (0-18 months) in Gayaman Village, Mojokerto Regency, who were obtained by purposive sampling. Measuring instruments were used to assess nutritional status and denver II forms to assess the progress. The research was done on July 28 to August 25, 2018. Statistical test used Wilcoxon Signed Rank Test. The results showed that nutritional status before being given touch therapy was normal as many as 57 (83%) respondents, and the development after being given touch therapy increased to 66 (96%) respondents. The development before being given touch therapy was normal as many as 27 (39%) respondents with Ï = 0.003. This showed that there was an effect on touch therapy to their nutritional status. The nutritional status after being given a touch therapy increased to 57 (83%) respondents with Ï = 0.008. This showed that there was an effect of touch therapy on their development. Massaging was a fun way to help strengthening the bond between mother and child. This was the key to baby's development.